Thrombotic thrombocytopaenic purpura masqueraded by severe dengue - Ruzanna Dayanna Zawawi; Asral Wirda Binti Ahmad Asnawi; Rashidah Mohamed; Jameela Sathar (Malaysian Society of Pathologists, 2024)
Introduction: Thrombotic thrombocytopenic purpura (TTP) is characterized by severe thrombocytopenia and microangiopathic hemolytic anemia. Although some patients also have a combination of fever and neurologic and/or renal manifestations, these are not essentially required for diagnosis. Ultra-large von Willebrand factor (vWf) multimers found in the patient's plasma are the basis for the platelet thrombi. Recent evidence has linked the abnormal fragments of vWf with deficiency of a plasma enzyme named vWf-cleaving protease or ADAMTS-13. Our aim is to raise awareness that clinical suspicion is paramount in clinching the diagnosis and highlight the importance of early detection and prompt management to improve patient's chance of survival. Case Report: We present a case of a 41-year-old Malay lady initially diagnosed with Severe Dengue, who subsequently demonstrated clinical and laboratory findings of TTP. When it was thought that she was recovering from the Dengue infection, she developed marked direct hyperbilirubinemia, which was quickly complicated by encephalopathy. Further laboratory investigations strongly pointed towards ongoing haemolysis with evidence of microangiopathic haemolytic anaemia. Despite, a within-range ADAMTS-13 level, three cycles of plasma exchange with fresh frozen plasma were promptly constituted to the patient of which she made a remarkable recovery. Discussion and Conclusion: The absence of severe ADAMTS-13 deficiency, as measured by current static assays, should not be used to argue against the use of plasma exchange, which has been highly effective even several years before the discovery of ADAMTS-13. Thus the determination of ADAMTS-13 activity has only a limited role in the diagnosis of TTP.